2020
DOI: 10.1111/ejss.12943
|View full text |Cite
|
Sign up to set email alerts
|

No‐till System Participatory Quality Index in land management quality assessment in Brazil

Abstract: Soil fertility is the result of interactions between the physical and chemical soil attributes, affecting its biological component, which in turn feeds back to the physical and chemical soil attributes. The No-Till System (NTS) is the main modality of Conservation Agriculture, essential to achieving farming sustainability and conserving soil fertility. However, farmers often fail to adopt the three principles of NTS: (a) minimum mechanical soil disturbance, (b) permanent soil cover and (c) plant diversificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
(47 reference statements)
0
17
0
1
Order By: Relevance
“…The NTS met the basic assumptions of permanent soil cover, crop rotation, and minimum soil disturbance (Nunes et al, 2020). The other farm systems grouped as the following descriptions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NTS met the basic assumptions of permanent soil cover, crop rotation, and minimum soil disturbance (Nunes et al, 2020). The other farm systems grouped as the following descriptions.…”
Section: Methodsmentioning
confidence: 99%
“…In the NTS, the continuous input of organic wastes is essential to the maintenance of the soil structure (Silva et al, 2014) and to increase the stability of the aggregates (Silva et al, 2011). The NTS has as its three main principles the minimum soil disturbance, crop rotation, and permanent soil cover, either by straw or living plants (Nunes et al, 2020). However, it is not always completely implemented, which results in the reduction of its benefits as a conservation practice (Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Farmers may often fail to adopt the principles and practices followed in NT. To tackle this problem, Nunes et al, 2020 focused on the three pillars of the NT system – minimum mechanical soil disturbance, permanent soil cover and plant diversity – and implemented a participatory quality index (PQI) in Brazil, which enabled the farmers to self‐assess and monitor soil management in an NT area. The tool was trialled on 40 areas of farmland under different farm systems in the Paraná River Watershed.…”
Section: Specific Nt Impacts On Physical Chemical and Biological Promentioning
confidence: 99%
“…Conservation agriculture (CA) (i.e., minimal soil disturbance, permanent soil cover, and crop rotation) is a major initiative promoted by the Food and Agriculture Organization of the United Nations (FAO-UN) and other institutions to recover SOC and provide climate change adaptation and mitigation (Jat et al, 2014). No-till (NT) agriculture is the basic component of CA by addressing at least two of its three principles (i.e., planting through soil cover with minimum soil disturbance) (Nunes et al, 2020). Several studies already showed that NT significantly increases SOC at the soil surface in a wide range of soils, climates, and cropping systems (West and Post, 2002;Ogle et al, 2005).…”
Section: Introductionmentioning
confidence: 99%